Does infertility develop posttraumatic growth or anxiety/depressive symptoms? Roles of personality traits, resilience, and social support. Issue 4 (8th January 2022) - Shafierizi, Shiva; Faramarzi, Mahbobeh; Esmaelzadeh, Seddigheh; Khafri, Soraya; Ghofrani, Faezeh
Abstract: Purpose: This study aimed to explore levels of posttraumatic growth (PTG) and anxiety/depressive symptoms and the role of personality traits, resilience, and social support as predictors of PTG in infertile men/women. Design and Methods: In our cross‐sectional study, 162 infertile individuals (40 men and 122 women) completed the research questionnaires, including PTG, State‐Trait Anxiety Inventory, Fertility Problem Inventory, NEO Five‐Factor Inventory, Perceived Social Support, Kobasa hardiness short 20‐item, and Beck Inventory Depression (BDI‐II). Results: The prevalence of PTG was higher than that of anxiety/depressive symptoms (55.6% vs. 45.7%/40.7%). Neuroticism ( β = 0.54 ± 0.25, p < 0.03), extroversion ( β = 0.69 ± 0.26, p < 0.01), and resilience ( β = 0.33 ± 0.12, p < 0.008) were positive predictors of PTG. Practice Implications: Infertile men/women with high level of resilience, extroversion, and neuroticism may have more tendency toward personal growth rather than distress. Practitioners ought to direct counseling to promote factors of personal growth.